3D MODELING AND DERIVATIVE ANALYSIS OF THE KETAHUN SEGMENT BASED ON GGMPLUS AND SRTM2 DATA FOR DISASTER MITIGATION - Clora Ulandari; Halauddin Halauddin; Refrizon Refrizon; Hilmi Zakariya; Suhendra Suhendra; Muchammad Farid; Alda Sulistiani; Hana Raihana; Nurul Apriyanti (Institut Teknologi Sepuluh Nopember, 2026)
interaction between the Sumatra subduction zone and the Sumatra Fault, resulting in high seismic activity. One of the important segments with the potential to cause earthquakes is the Ketahun Segment in Lebong Regency, Bengkulu Province. This study aims to map the three-dimensional (3D) fault structure and identify lithological density contrasts to support disaster mitigation efforts. The methods used include processing GGMPlus and SRTM2gravity satellite gravity data, complete Bouguer correction, regional-residual anomaly separation, first horizontal derivative (FHD) and second vertical derivative (SVD) analysis, and 3D inversion modeling using Grav3D software. The CBA analysis results show anomaly values of –8 to 50 mGal with sharp gradations indicating the presence of major fault structures. SVD and FHD analyses show the dominance of dip-slip faults with significant density contrasts. The 3D inversion modeling shows a density range of 1.02–3.52 g/cm³ with an average value of 2.27 g/cm³, where the low-density zone is at a shallow depth (0–1500 m) and the high-density zone is at a depth of 500–2000 m. The sharp boundary between the two zones indicates an active fault plane at a depth of 1000–2500 m. These findings provide a more representative picture of the fault geometry and can be used as a basis for developing earthquake mitigation strategies and spatial planning based on actual geological conditions in the Bengkulu region.